2020
DOI: 10.1088/1361-6595/ab5da3
|View full text |Cite
|
Sign up to set email alerts
|

Ozone and oxygen atoms production in a dielectric barrier discharge in pure oxygen and O2/CH4 mixtures. Modeling and experiment

Abstract: This paper describes the results of modeling of a dielectric barrier discharge (DBD). Filamentary structure of DBD is taken into account in the model by introducing the ratio of the cross section area of a microdischarge to the electrode area as a parameter of the model. Discharge and afterglow stages in the gas flow were studied using a zero-dimensional model for a DBD microdischarge channel. The results of modeling are compared with literature data for [O] number densities in a single pulse nanosecond disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 36 publications
1
22
0
1
Order By: Relevance
“…Therefore, decrease in [O 3 ] with power load and [CH 4 ] resulted from temperature rise, that slowed ozone formation rate, and destruction of O 3 by the chain mechanism initiated by H atoms, appeared as the result of partial CH 4 dissociation. The model and the experiment [14] exhibited satisfactory agreement for the O 2 /CH 4 mixtures with relatively large equivalence ratios (ϕ = 0.22 and 0.44). However, later we found that model [14] could not adequately describe formation of O 3 in air and in air/CH 4 and O 2 /CH 4 mixtures with relatively small additions of methane.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Therefore, decrease in [O 3 ] with power load and [CH 4 ] resulted from temperature rise, that slowed ozone formation rate, and destruction of O 3 by the chain mechanism initiated by H atoms, appeared as the result of partial CH 4 dissociation. The model and the experiment [14] exhibited satisfactory agreement for the O 2 /CH 4 mixtures with relatively large equivalence ratios (ϕ = 0.22 and 0.44). However, later we found that model [14] could not adequately describe formation of O 3 in air and in air/CH 4 and O 2 /CH 4 mixtures with relatively small additions of methane.…”
Section: Introductionmentioning
confidence: 74%
“…The model and the experiment [14] exhibited satisfactory agreement for the O 2 /CH 4 mixtures with relatively large equivalence ratios (ϕ = 0.22 and 0.44). However, later we found that model [14] could not adequately describe formation of O 3 in air and in air/CH 4 and O 2 /CH 4 mixtures with relatively small additions of methane.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Figure 4 a shows the schematic of the procedure adapted for the 0-D chemical kinetics simulation. The VIBRKIN reactor module of Chemical Workbench software, a well-developed and proprietary software of M/s Kintech Laboratory 41 was used to solve the non-equilibrium plasma reactions together with the heavy particle reactions 26 , 42 45 . A total of 81 species were included in the model, which react to each other through 274 reactions, detailed in Table SI of the Supplementary Material.…”
Section: Methodsmentioning
confidence: 99%
“…The VIBRKIN reactor model available in the Chemical Workbench software of M/s Kintech Laboratory [45] was used to solve the nonequilibrium plasma reactions together with the thermal reactions [46][47][48][49]. A total of 53 processes were included in the mechanism to describe the N 2 -RGA discharge as best as possible, shown in table SII of the supplementary material.…”
Section: Chemical Workbench Simulationmentioning
confidence: 99%